Resenhas - Nuernberg, Adriano; Ferreira, Ana Paula; Soria, Analía; Gómez, Antonio Castillo; Sayão, Deborah Thomé; Pirani, Denise; Herrera, Gioconda; Viviani, Luciana Maria; Vieira, Daiane Antunes; Yannoulas, Silvia Cristina; et al. (Revista Estudos Feministas, 2001)
Resenhas